Environmental savings in tomato production under optimal agrochemicals management: a modeling approach (2017)
The use of agrochemicals has been recognized as one of the main environmental burdens in agriculture. Actual management practices aggravate pollution issues due to overdosing and untimely applications, even more if farmers are reluctant to change their practices. The application of crop modeling coupled to environmental impact tools offers an alternative to analyze improved production scenarios. The objective of this study was to estimate the environmental savings due to optimized agrochemicals management for tomato production in Colombia. For this purpose, we calibrated a generic growth model for greenhouse tomatoes. The environmental performance of the current and optimized schemes was evaluated through a life-cycle assessment (LCA) approach. Data for current practices were collected through detailed follow-ups of 38 growing cycles. The optimized scenario was constructed by simulating crop growth based on the climate for each cycle. These scenarios also considered optimized nitrogen fertilization and restricted use of pesticides. All resource consumption and emissions referred to a functional unit of 1 t tomatoes with boundaries defined from raw material extraction to farm gate. The assessment considered the manufacture and emissions to water and soil of nitrogen fertilizers and pesticides. Average observed and simulated yield were 83.3 and 178.5 t ha-1, respectively. Most of the reductions due to the optimal strategy were above 90% for most of the impact categories. Under the actual production strategy, the manufacture of N fertilizers was the main contributor to the environmental impact for most categories. The impact of N field emissions was more relevant under the optimal model, since the shares of this component were 26.1, 74.7, and 95.1% for acidification potential, eutrophication potential, and global warming potential, respectively. The optimized scenario showed that there is huge room to improve Colombian tomato production technically and environmentally.